PASINDEN: AWAL KEHADIRANNYA DALAM PERTUNJUKAN WAYANG GOLEK - Tarjo Sudarsono (Paraguna, 2018)
In  1930  Sinden  became part of the  Wayang Golek show.  This phenomenon is  the creativity  of the  puppeteer Baraja  who  was   not  satisfied  with  the  conventional wayang   gol~k    performance.    Finally     Sinden     presented   songs     that     was entertainment   in   Wayang   Golek   show  performances.   Furthermore,   the   other puppeteers imitated   him  and  in the  end  the  sind~n  and  the puppeteers  became a unity  called the "Dwi Tunggal"  who complemented and worked together  in the performance.  In the  beginning,  the presence of sind~n  in the  Waang  Golek  show gave   the  famous  sind~n   in  the  community.  They   have  the  name   code  (popular name)    and   the   song    that characterizes   them.   This  phenomenon  shows   the dynamism of a traditional form ofperformance in the supporting community.